Letter: the gap between guidelines and real clinical practice for dysplasia surveillance in inflammatory bowel disease. Issue 4 (28th January 2020) - Mocciaro, Filippo; Scimeca, Daniela; Conte, Elisabetta; Bonaccorso, Ambra; Magro, Bianca; Lo Mastro, Michela; Di Mitri, Roberto
Abstract : LINKED CONTENT This article is linked to Iannone et al paper. To view this article, visit https://doi.org/10.1111/apt.15493 .